PEMETAAN DAERAH RAWAN BANJIR DI DESA MOJOREJO KOTA BATU MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Rizky Ahmad Qusyairy; Fahmi Nur Hakim; Nia Putri Nabila; Dieksa Saputri Himawan; Muhammad Rijal Raharjo; Artika Putri Devi Arifianto; Anggraini Erika Putri; Yosefa Martha Mutiarakasih; Weldys Febri Yulianto; Rizal Aldi Ramadani; Rayana Sulthon Ar Rabbani; Rangga Putra Kusuma; Fajri Ramli; Nurul Huda Romadhoni; Eqsa Citra Efanda Neni; Puput Risdanareni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to map flood-prone areas in Mojorejo Village, Junrejo District, Batu City, using a Geographic Information System (GIS) approach. Methodologically, a multi-criteria overlay analysis was applied within ArcGIS software by integrating six spatial parameters: slope, elevation, soil type, rainfall, land cover, and drainage density. Each parameter was classified, scored, and weighted based on its relative influence on flood generation. The weighting scheme assigned 30% to slope, 25% to rainfall, 20% to land cover, 15% to elevation, 10% to drainage density, and 5% to soil type. The spatial analysis reveals that flood vulnerability in Mojorejo Village is heavily driven by the intersection of flat terrains and high-intensity rainfall, which significantly trigger surface runoff. This condition is aggravated by high soil saturation from low-permeability clay soils and accelerated land conversion into residential or commercial zones that reduces soil infiltration. The resulting flood vulnerability map serves as an essential spatial decision-support tool for the local government and community to implement strategic, risk-based structural and non-structural flood mitigation planning.